Pengalaman Kerja, Tingkat Pendidikan, Pelatihan dan Efektivitas Penggunaan Sistem Informasi Akuntansi di Koperasi Simpan Pinjam - Ribeiro, Flora Angela; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 33 No 5 (2023), 2023)
The research aims to determine the effect of work experience, education level, and training on the effectiveness of using accounting information systems in savings and loan cooperatives in South Denpasar District. The samples used were 18 cooperatives with 54 respondents by applying a purposive sampling technique. Data was collected through the questionnaire method which was then analyzed using multiple linear regression tests which were processed with the help of the SPSS 24.0 application. The results of the study show that work experience, level of education, and training have a positive and significant influence on the effectiveness of using accounting information systems in savings and loan cooperatives in South Denpasar District. Keywords: Work Experience; Education Level; Training; Effectiveness of Use of Accounting Information Systems.